Efficient selection and evaluation of suppliers: a model for a microenterprise in the textile sector in Lima, Peru - Cornejo-Cabanillas, Katya (2022)
n Peru, the textile sector has experienced a decline in recent years and generates a significant number of direct and indirect jobs. One of the main causes of this is a destabilized supply chain, and supplier management is one of the main obstacles. To improve the fulfillment of the orders of the companies with their final customers, be competitive and to establish a balance and good agreements with their suppliers in a situation of uncertainty, with this study a supplier management model has been developed. It is based on Supply Chain Reference Model and Supplier Potential Matrix which give the framework to evaluate those suppliers who can help to streamline the supply chain. The success of the study is reflected on savings and time reduction for the procurement process.